1995
DOI: 10.1172/jci118153
|View full text |Cite
|
Sign up to set email alerts
|

Lactation as a model for naturally reversible hypercorticalism plasticity in the mechanisms governing hypothalamo-pituitary- adrenocortical activity in rats.

Abstract: Steady state levels of hypothalamic expression of the genes encoding corticotropin-releasing hormone (CRH), proopiomelanocortin (POMC), arginine vasopressin (AVP), and oxytocin (OT) were studied in rats to investigate the mechanisms underlying the transitions between hypercorticalism during lactation and normocorticalism upon weaning. During lactation, CRH mRNA levels and blood titers of adrenocorticotropin (ACTH) were found to be significantly reduced, although POMC mRNA levels in the anterior pituitary were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
62
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 47 publications
(35 reference statements)
6
62
0
Order By: Relevance
“…As a consequence, the hypothalamic feedback on CRH secretion is removed, which leads to an enhanced activation of brain CRH peptide synthesis (O'Keane et al 2011). Our finding of an enhanced expression of Crh mRNA in the PVN is similar to the findings of a study carried out in 3-day-old lactating rats of the Sprague Dawley strain (da Costa et al 2001) and are in accordance with higher Crh mRNA levels found in the PVN of chronically stressed animals (Pournajafi-Nazarloo et al conditions (Fischer et al 1995, Brunton et al 2008. As the CRH levels were found to be low during pregnancy (Neumann et al 1998) and HPA axis reactivity was restored within 2 days of pup removal (Walker et al 1992, Toufexis et al 1999, it can concluded that the stage of the lactation period obviously influences the outcome of this type of analysis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As a consequence, the hypothalamic feedback on CRH secretion is removed, which leads to an enhanced activation of brain CRH peptide synthesis (O'Keane et al 2011). Our finding of an enhanced expression of Crh mRNA in the PVN is similar to the findings of a study carried out in 3-day-old lactating rats of the Sprague Dawley strain (da Costa et al 2001) and are in accordance with higher Crh mRNA levels found in the PVN of chronically stressed animals (Pournajafi-Nazarloo et al conditions (Fischer et al 1995, Brunton et al 2008. As the CRH levels were found to be low during pregnancy (Neumann et al 1998) and HPA axis reactivity was restored within 2 days of pup removal (Walker et al 1992, Toufexis et al 1999, it can concluded that the stage of the lactation period obviously influences the outcome of this type of analysis.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that although ACTH is derived from POMC, we failed to detect significant differences in resting plasma ACTH levels. Obviously, the increased synthesis of the precursor mRNA is not necessarily paralleled by a similarly increased release of ACTH, as has been suggested earlier (Fischer et al 1995). Further studies have to determine whether an enhanced synthesis of Pomc mRNA may provide an alternative marker for a chronic stress state (Makara et al 2012).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…During lactation, the activity and regulation of the HPA axis are altered in ways that are dependent on the presence or suckling of the young (Walker, Lightman, Steele & Dallman, 1992;Windle et al 1997). Thus, an increase in glucocorticoid secretion and a flattening of the diurnal rhythm in glucocorticoid secretion have been described (Stern, Goldman & Levine, 1973;Walker et al 1992;Fischer, Patchev, Hellbach, Hassan & Almeida, 1995). In addition, secretion of ACTH from the anterior pituitary and, consequently, of cortisol (humans) and corticosterone (rats) from the adrenal glands is reduced during physical (Altemus, Deuster, Galliven, Carter & Gold, 1995;Walker, Trottier, Rochford & Lavall ee, 1995), ether (Lightman & Young, 1989;Walker et al 1992) and noise stress (Windle et al 1997), and in response to cardiovascular stimuli (Keller-Wood, 1996).…”
mentioning
confidence: 99%